Lithium Nitrate Solvation Chemistry in Carbonate Electrolyte Sustains High‐Voltage Lithium Metal Batteries - Yan, Chong; Yao, Yu‐Xing; Chen, Xiang; Cheng, Xin‐Bing; Zhang, Xue‐Qiang; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2018)
The lithium metal anode is regarded as a promising candidate in next‐generation energy storage devices. Lithium nitrate (LiNO3) is widely applied as an effective additive in ether electrolyte to increase the interfacial stability in batteries containing lithium metal anodes. However, because of its poor solubility LiNO3 is rarely utilized in the high‐voltage window provided by carbonate electrolyte. Dissolution of LiNO3 in carbonate electrolyte is realized through an effective solvation regulation strategy. LiNO3 can be directly dissolved in an ethylene carbonate/diethyl carbonate electrolyte mixture by adding trace amounts of copper fluoride as a dissolution promoter. LiNO3 protects the Li metal anode in a working high‐voltage Li metal battery. When a LiNi0.80Co0.15Al0.05O2 cathode is paired with a Li metal anode, an extraordinary capacity retention of 53 % is achieved after 300 cycles (13 % after 200 cycles for LiNO3‐free electrolyte) and a very high average Coulombic efficiency above 99.5 % is achieved at 0.5 C. The solvation chemistry of LiNO3‐containing carbonate electrolyte may sustain high‐voltage Li metal anodes operating in corrosive carbonate electrolytes. Liquid assets: LiNO3 can be dissolved directly in an ethylene carbonate/diethyl carbonate electrolyte mixture by adding a trace amount of copper fluoride to promote dissolution. The solvation structure of the electrolyte system protects the lithium metal anode in a working high‐voltage lithium metal battery. NCA=LiNi0.80Co0.15Al0.05O2.